Latin American Stereotypes in Finnish Social Media - Jussi Pakkasvirta (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies, 2018)
Communication has always been a prominent part to produce national stereotypes. The familiar patterns of collective and communicative action are associated with nation-building processes, which acquired great amounts of organizational resources in modern political communities beginning in the nineteenth century. These “modern” processes created strong collective national identities. Since the Internet era, we have encountered new and less familiar logics of connective action based on personalized content sharing across various media networks. Introducing digital media does not dramatically change the core dynamics of traditional community-building processes, but the logic of connective action does. This article analyzes one case of our era: how Latin American stereotypes are present in Finnish social media, and what new insights the method – the analysis of social media big data – would bring. Likewise, the article studies Finnish nationalism – how Finnish people see themselves when explaining other national cultures. The central questions stem from media discussions about Latin American countries: How are concepts and words referring to Latin America used in Finnish social media, and how does this kind of interaction is built on and further strengthen national or “continental” historical stereotypes, repeated again in new media forums? Latin American stereotypes serve also as social media representations to reflect Finnish national self-portrait.1